Quality of Epididymal and Ejaculated Sperms of Spotted Buffalo in Dextrose Supplemented Extender - . Yulnawati; Muhammad Gunawan; Hera Maheshwari; Muhammad Rizal; . Herdis; Arief Boediono (HAYATI Journal of Biosciences, 2010)
Quality of epididymal and ejaculated sperms of spotted buffalo in three different extenders (i.e. Andromed, Andromed supplemented with 0.2% dextrose, and Andromed supplemented with 0.4% dextrose) was studied.  The results showed that there was no significantly different (P > 0.05) quality of ejaculated and epididymal sperms.  The motility percentage of post thawing epididymal and ejaculated sperms was 41-46% and 41-45%, respectively.  And percentage of cytoplasmic membrane integrity of the post thawing epididymal and ejaculated sperms was 66-67% and 47-54% respectively. There was also no significant different (P > 0.05) in the percentage of cytoplasmic membrane integrity between the extenders of both ejaculated and epididymal sperms. This result suggested that epididymal sperms were reliable for artificial insemination as good as ejaculated sperms.